Melatonin, leptin, and ghrelin levels in nurses working night shifts - Söylemez, Sibel; Çaycı Sivri, Ayşe Banu; Şimşek, Ercan; Polat, Burçak; Çakır, Bekir (Journal of Surgery and Medicine, 2019)
Aim: The levels of several hormones including melatonin, leptin, and ghrelin are regulated by circadian rhythm. Deregulated hormone levels due to disruption of circadian rhythm may result in medical conditions like metabolic syndrome (MetS). The aim of this cross-sectional study was to investigate the associations among circadian rhythm, melatonin, leptin, ghrelin and metabolic syndrome by determining melatonin levels of healthy nurses who were working on night-shift for at least 3 months and of those on day-shift for at least 3 months. Methods: Venous bloods following 8-hour fasting of 50 nurses, who were aged at 20-40 age range and whose Body Mass Index (BMI) were >25, were collected. Those working on night-shift were named as night group and the control group of the study was named as day group. From the bloods collected; melatonin, leptin and ghrelin levels were evaluated by ELISA method, insulin was evaluated by immunochemically, whereas fasting blood glucose, cholesterol, triglyceride, high-density lipoprotein (HDL) and low-density lipoprotein (LDL) levels were evaluated spectrophotometrically. Results: Melatonin level was significantly lower in the night-shift group compared to the day-shift group (p=0.003). Leptin level was slightly but not significantly lower in the night-shift group (p=0.097). In contrast, ghrelin level and other biochemical parameters including triglyceride, fasting blood sugar (FBS), insulin, insulin resistance index (HOMA-IR) and cholesterol were increased in the night-shift group but these increments were not statistically significant. Conclusion: Our results suggest that night-shift work might exhibit tendency towards MetS by disrupting circadian rhythm.